The ownership structure, and the environmental, social, and governance (ESG) disclosure, firm value and firm performance: The audit committee as moderating variable - Luk Luk Fuadah; Mukhtaruddin; Isni Andriana; Anton Arisman (Economies, 2022)
This study investigated the effect of ownership structure on environmental, social, and governance (ESG) disclosure, firm value, firm performance, and audit committees as moderating variables in the Indonesian context. The ownership structures in this study are foreign, public, state, and family ownership. This research is quantitative and uses secondary data. The sample consisted of 140 companies on the Indonesia Stock Exchange for the 2018-2020 period. This study used legitimacy, stakeholder, and agency theory. The analytical method used was partial least squares structural equation modeling. The results show that foreign and public ownership positively and significantly affect environmental, social, and governance disclosure. However, state and family ownership did not affect environmental, social, and governance disclosure. In addition, environmental, social, and governance disclosure positively impacts firm value. However, environmental, social, and governance disclosure do not affect a company's performance. Audit committees moderate the influence of environmental, social, and governance disclosure and firm value. However, the audit committees do not moderate the effect of environmental, social, and governance disclosure and firm performance. The government should make stronger environmental, social, and government regulations that must be implemented by companies listed on the Indonesia Stock Exchange even though they are now voluntary.
Keywords: 330; and governance (ESG) disclosure; audit committee; environmental; firm performance; firm value; ownership structure; social